Mechanistic insights into the cancer cell cytotoxicity and blood stability of the garlic compound ajoene - Kusza, Daniel Andreas (Department of Chemistry, 2017)
Ajoene, a garlic-derived natural product and its structural analogues are strongly cytotoxic to cancer cells. These compounds are however known to exhibit low blood stability and erythrocyte toxicity. This thesis reports on the synthesis of eight ajoene analogues designed to probe structure-activity relations into cancer cell cytotoxicity and blood stability. Structural variations included introduction of different solubility enhancing terminal groups (amide and phenol) as well as variations in the sulfoxide / vinyl-disulfide core. The phenol ajoene analogues were found to be more cytotoxic against WHCO1 oesophageal cancer cell proliferation than the corresponding amides. The structureactivity data support a thiolysis mechanism where ajoene forms a mixed disulfide with a reactive cysteine residue on a protein target which leads to both its cytotoxicity and blood instability. This in turn is mediated by the reactivity of the disulfide pharmacophore which is enhanced by the vinyl group. The sulfoxide functional group is perceived as modulating disulphide reactivity by an inductive electron-withdrawal through the aliphatic σ-framework. The dihydroajoenes emerged as attractive candidates for further cancer therapeutic development with improved blood stability with a half-life around 120 minutes and good cancer cell cytotoxicity (IC₅₀ of approximately 20 μM). A spectrophotometric and proteomic binding study demonstrated S-thiolation between ajoene and the cysteine 93 residue in the -subunit of haemoglobin which may explain the observed blood instability. A biotinylated ajoene analogue was designed and synthesised to identify ajoene's protein targets within the cancer cell. This was achieved using a convergent "Click"-strategy, involving azidated ajoene and biotin-alkyne. Both the biotin-ajoene and the azide-ajoene showed strong cytotoxicity against WHCO1 cancer cells. An immunoblotting experiment showed the successful biotinylation of haemoglobin, as a model protein by both whole probe and an in situ "Click"-reaction. This biotinylated probe can be used in future work to identify the ajoene protein targets in cancer cells.